2021
DOI: 10.3390/cancers13143408
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Cancer Vaccination with Immunopeptidomics-Discovered Antigens Confers Protective Antitumor Efficacy

Abstract: Knowledge of clinically targetable tumor antigens is becoming vital for broader design and utility of therapeutic cancer vaccines. This information is obtained reliably by directly interrogating the MHC-I presented peptide ligands, the immunopeptidome, with state-of-the-art mass spectrometry. Our manuscript describes direct identification of novel tumor antigens for an aggressive triple-negative breast cancer model. Immunopeptidome profiling revealed 2481 unique antigens, among them a novel ERV antigen origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
(55 reference statements)
3
21
0
Order By: Relevance
“…Specifically, PeptiCRAd combines the immunogenicity of the adenovirus with the tumor specificity conferred by the peptides, eliciting a strong anti-tumor immune response. In this study, we showed that PeptiCRAd technology was successfully used to treat the established mesothelioma tumor model in vivo, providing a proof-of-concept that peptides identified by immunopeptidomics can be used for the development of cancer vaccines, as we have also previously demonstrated for other tumor models (14,16).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Specifically, PeptiCRAd combines the immunogenicity of the adenovirus with the tumor specificity conferred by the peptides, eliciting a strong anti-tumor immune response. In this study, we showed that PeptiCRAd technology was successfully used to treat the established mesothelioma tumor model in vivo, providing a proof-of-concept that peptides identified by immunopeptidomics can be used for the development of cancer vaccines, as we have also previously demonstrated for other tumor models (14,16).…”
Section: Discussionsupporting
confidence: 59%
“…PeptiCRAd complexes were prepared as previously described elsewhere (13)(14)(15)(16). Briefly, complexes were formed by mixing Ad5/3-D24 virus and peptides with a poly K tail (in PBS) at a ratio of 20μg of peptides per 1x109 VP per mouse in minimum volume.…”
Section: Pepticrad Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…PeptiCRAd consists of an OAd coated through electrostatic interactions with positively charged MHC-I restricted tumor peptides (poly-lysine tail-peptides) ( 26 ). The reaction requires only 15 minutes and several studies have shown its anti-tumor efficacy and immunological modulation in different contexts and tumor models such as murine triple-negative breast cancer ( 34 ), as a cancer therapeutic platform for immunopeptidomic pipelines ( 7 , 35 ), as a tool to explore viral mimicry to tumor antigens for cancer immunotherapy ( 36 ), as a platform to exploit pre-existing immunity to pathogens for boosting anti-tumoral CD8 T cell response ( 37 ) or to decorate with tumor peptides OAd encoding immunostimulatory molecules ( 38 ). However, we have never compared our cancer vaccine platform with traditional approaches in the field such as OAd genetically modified to encode TAs.…”
Section: Discussionmentioning
confidence: 99%